The influence of Service Quality, Innovation, and Customer Satisfaction on User Compliance (Literature Review) - Surahman, Surahman (Dinasti International Journal of Digital Business Management, 2023)
The Literature Review article titled "The Effect of Service Quality, Innovation, and Customer Satisfaction on User Compliance" aims to form research hypotheses regarding the influence of variables that can be used for further research in the field of Financial Management. The method used in writing this article is the library research method, with sources of information from online media such as Google Scholar, Mendeley, and other academic sources of information. The results of this literature review article conclude that: 1) Service Quality affects User Compliance; 2) Innovation affects User Compliance; and 3) Customer Satisfaction affects User Compliance.